Pemanfaatan Animasi sebagai Media Pembelajaran Berbasis Teknologi untuk Meningkatkan Motivasi Belajar - Eka Melati; Ayyesha Dara Fayola; I Putu Agus Dharma Hita; Andi Muh Akbar Saputra; Zamzami Zamzami; Anita Ninasari (Departement of Mathematics Education, 2023)
This study examines the utilization of animation as a technology-based learning media to enhance student motivation. In the midst of rapid advancements in information and communication technology, education requires innovative transformation in learning methods. Animation has been recognized as an effective tool to enrich student learning experiences through clear and interactive visual representations. The aim of this research is to analyze literature related to the utilization of animation as a learning media, explore its benefits and challenges, and convey the contribution of this study to the development of innovative learning practices. The method employed in this research is literature review, where data is obtained through analysis of theoretical sources and relevant studies. The results of the literature analysis indicate that animation holds great potential in enhancing student motivation, engagement, creativity, and personalized learning. However, it is crucial for educators and researchers to pay attention to good animation design and the role of educators in facilitating effective animation utilization. This research contributes to the development of innovative learning practices and enriches the understanding of the utilization of animation as an effective learning media in enhancing student motivation.